From Despair to Faith: A Stylistic Exploration of Kierkegaard’s Existentialism in Sutardji Calzoum Bachri’s “Nuh” - Amalia, Anindita Fikri; Nurjanah, Sindah Laili; Vina Uctuvia (Surakarta English and Literature Journal, 2025)
This study uses stylistic analysis with a qualitative descriptive method to looking for the representation of the three stages of human existence based on Soren Kierkegaard's existential philosophy in the poem “Nuh” by Sutardji Calzoum Bachri. Poetry was chosen as the object of research because it has the power of spiritual symbolism and complex existential themes. The analysis focuses on how the physical structural elements of the poem such as diction, figurative language, and imagery show that Kierkegaard's three stages of existence that is aesthetic, ethical, and religious. The results of the study show that the depiction of despair, suffering, and darkness in the first stanza represents the emergence of the aesthetic stage. The repetition of the word /tanah/ (land) which symbolizes moral awareness and surrender represents the emergence of the ethical stage. The plea for a /puncak/ (peak) which depicts spiritual hope and total surrender to God show that the emergence of the religious stage. This poem recounts the poet’s spiritual experience and depicts a broad existential journey from despair to transformation. “Nuh” combines poetic language with philosophical depth to interpret existential allegories.